James Gray (?1770–1830): East India Company chaplain - Jasper, David (Theology (Norwich), 2024)
James Gray was for most of his professional life a school master in Dumfries and Edinburgh. He was also a poet in touch with the major talents of his day. Of humble Scottish origins, in later life he was ordained as an Anglican priest and was for three years a chaplain in the East India Company, serving in the remote post of Bhuj in Cutch. His short ministry was remarkable as he translated the Gospels into Hindustani and the local language of Kachchi, founded a school, and was private tutor to the local ruler or Rao. In many ways he was far ahead of his time. He died in Bhuj after only three years of service there.